Revision of the South American species of Neralsia (Hymenoptera: Figitidae) with the description of eight new species - Jiménez, M. (2008)
Neralsia is a genus of Figitid hymenopterans present in both the Neartic and the Neotropical regions. In this work, material from several museums (including all types of the South American species of Neralsia) was analyzed with light and electron microscopy. The South American species are studied as a whole, reviewing 26 previously cited species and describing eight new species. A key for their identification is included and the characters to differentiate species here considered are illustrated.